Hymenoptera marking technique - Pereira, A. M. [UNESP]; Chaud-Netto, J. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
In true social hymenopterans, such as many species of bees, wasps and all species of ants, the main characteristics are the overlapping of generations, the care with the offspring and the division of labor among the members of the colony. The first biological feature means that in a same moment there are groups of individuals, with variable ages, that execute different activities in the colony. In order to study the division of labor among the members of the colony, or to estimate the life span of these insects, or even to analyze any kind of behavior in non-social insects, it is necessary to know the exact age of each individual. For this reason, the insects must be identified soon after emergence. The identification of insects with numbers is an important technological improvement in behavioral studies, mainly in honeybee colonies. The aim of this scientific note is to describe an easy and cheaper technique for marking hymenopterans.
Keywords: Apis mellifera; Hymenoptera; marking technique; social insects